The association between higher maternal pre-pregnancy body mass index and increased birth weight, adiposity and inflammation in the newborn - McCloskey, K; Ponsonby, A; Collier, F; Allen, K; Tang, M; Carlin, J; Saffery, R; Skilton, M; Cheung, M; Ranganathan, S; Dwyer, T; Burgner, D; et al. (Wiley, 2016)
BACKGROUND: Excess adiposity and adiposity-related inflammation are known risk factors for cardiovascular disease in adults; however, little is known regarding the determinants of adiposity-related inflammation at birth. OBJECTIVES: The aim of this study was to investigate the association between maternal pre-pregnancy BMI and newborn adiposity and inflammation. METHODS: Paired maternal (28-week gestation) and infant (umbilical cord) blood samples were collected from a population-derived birth cohort (Barwon Infant Study, n = 1074). Data on maternal comorbidities and infant birth anthropomorphic measures were compiled, and infant aortic intima-media thickness was measured by trans-abdominal ultrasound. In a selected subgroup of term infants (n = 161), matched maternal and cord lipids, high-sensitivity C-reactive protein (hsCRP) and maternal soluble CD14 were measured. Analysis was completed by using pairwise correlation and linear regression. Because of their non-normal distribution, pathology blood measures were log transformed prior to analysis. RESULTS: Maternal pre-pregnancy BMI was positively associated with increased birth weight (mean difference 17.8 g per kg m(-2) , 95% CI 6.6 to 28.9; p = 0.002), newborn mean skin-fold thickness (mean difference 0.1 mm per kg m(-2) , 95% CI 0.0 to 0.1; p < 0.001) and cord blood hsCRP (mean difference of 4.2% increase in hsCRP per kg m(-2) increase in pre-pregnancy BMI, 95% CI 0.6 to 7.7%, p = 0.02), but not cord blood soluble CD14. Inclusion of maternal hsCRP as a covariate attenuated the associations between pre-pregnancy BMI and both newborn skin-fold thickness and cord blood hsCRP. CONCLUSION: Higher maternal pre-pregnancy BMI is associated with increased newborn adiposity and inflammation. These associations may be partially mediated by maternal inflammation during pregnancy.